Pengembangan Sistem Informasi Kehadiran Berbasis Android - Nuris, Nisa Dienwati; Sunarto; Yulistriani (LPPM UNIKA Santo Thomas Medan, 2022)
Data collection on student attendance at the Lestari Gumulunglebak Vocational High School (SMK) is carried out every day during teaching and learning activities to find out students who are unable to attend with information on permission, illness, neglect and other reasons. But in attendance data collection is still done manually in the form of paper documents and printed Microsoft Excel, then the teacher calls the names of students one by one so it is less effective and efficient because the results of attendance data are not accurate according to actual conditions. The system built produces a system that can improve the accuracy of student attendance data at school. This web-based system can facilitate the processing of attendance data at the SMK Lestari Gumulung Lebak school. This system can be a recommendation for the SMK Lestari Gumulung Lebak school